The Potential of Li-Fi for High-Speed Underwater Data Transfer - Abhishek G. Mudhol; S. A. Shirsat; Vishal R. Puri; Jayesh S. Pinjarkar (International Journal of Electrical and Communication Engineering Technology, 2024)
Recently, there has been a growing interest in using underwater communication (UC) to monitor obstacles and marine life in oceans. Unlike conventional methods which struggle due to the absorption of radio waves in water, Li-Fi technology has emerged as a promising solution. Li-Fi utilizes light to transmit data, making it effective for underwater communication as light can penetrate deep into the ocean. In a recent study, researchers successfully demonstrated real-time audio transmission using a Li-Fi transmitter. Remarkably, this system achieved a maximum transmission distance of 100 m underwater, showcasing its potential for various applications in marine environments. The system performance is analysed in terms of intensity, and distance. This system is simulated on proteus to transfer data in real time. The system demonstrates the transfer of voice signal with the help of Li-Fi communication. The unique transmission properties of the undersea environment have long posed challenges for underwater communication. Conventional techniques, such as radio frequency and acoustic communication, are limited by high attenuation and slow data transfer rates, respectively. Light Fidelity (Li-Fi), a wireless communication system that uses visible light, offers a promising solution for high-speed data transfer underwater. This article explores the potential of Li-Fi in addressing underwater communication challenges. It discusses the fundamentals of Li-Fi, its advantages over traditional methods, and the technical difficulties associated with its implementation in underwater environments. Additionally, potential use cases are highlighted, including military applications, underwater robotics, and oceanographic research.
Keywords: Underwater Li-Fi wireless; leaser; optical beam propagation; underwater communications (UC); wireless communications (WC)